The effect of mindfulness meditation on HPA - axis in pre-competition stress in sports performance of elite shooters - John, S.; Verma, S. K.; Khanna, G. L. (National Journal of Integrated Research in Medicine, 2011)
Little has been known about the Hypothalamic Pituitary Adrenal (HPA) axis response to pre-competition stress (PCS) and its response to relaxation therapies such as of Mindfulness Meditation Therapy (MMT) on sports population. In shooting sports good physical as well as psychological condition is highly demanded. Researchers have been performed on the psychophysiological responses of MMT on normal and diseased persons, but little has been done on sports population especially in shooters. Objective: The purpose of current study was to estimate the contribution of MMT on Salivary Cortisol (SC), a reliable physiological marker of HPA-axis response in reducing PCS, and its effect on shooting performance (PS). Methods: 96 male elite Shooters, with mean age of 29.5±4.3years were examined as in experimental and control (48 in each). Total duration of the study was five weeks, four weeks of experimental and one week study to determine the follow-up effect. Pre, post and follow-up data of quantitative phenotypic markers of HPA-Axis activity by analysis of SC and PS were analyzed. Results: Compare to control, experimental group has shown significant result, post-intervention (p<0.001) and in follow-up (p<0.001) in SC and in PS. Resulted in reduction of PCS level and increase in PS, whereas the control group has been shown non-significantresult (p<0.05). Conclusions: Results indicated that relaxation therapies such as MMT may decrease PCS and will enhance PS. It is concluded that in four weeks of MMT has an effect on HPA-Axis by decreasing the level of SC as a reliable physiological marker of PCS.